Assessing the Role of Product and Halal Label in Shaping Consumer Behavior: A Study of Purchasing Decisions in East Java - Sopingi, Imam; Zaki, Irham; Haryanti, Peni; Santoso, Rohmad Prio; Asri, Muhammad Rizal (Tribakti: Jurnal Pemikiran Keislaman, 2025)
This study aims to analyse the influence of halal products and halal labels on Generation Z's purchasing decisions, considering product quality, brand perception, and price as mediating variables. The trend of increasing awareness of halal products among young consumers, this study focuses on the role of these factors in shaping purchasing decisions. The research method used is quantitative with a survey approach, involving 523 respondents from five districts and cities in East Java (Jombang, Kediri City, Kediri Regency, Tulungagung, and Trenggalek) selected through purposive sampling. The results showed that halal products affect product quality, which in turn affects purchasing decisions through price. Halal labelling, although it has an effect on brand perception, does not show a direct effect on price or purchasing decisions through brand perception and price. This study provides new insights into how halal, quality and price factors are interrelated in influencing Generation Z's purchasing behaviour, as well as the importance of product quality as a key factor in halal value-oriented purchasing decisions.